Conditions at the time of inoculation influence survival of attenuated Escherichia coli O157:H7 on field-inoculated lettuce. (February 2020) - Moyne, Anne-laure; Blessington, Tyann; Williams, Thomas R.; Koike, Steven T.; Cahn, Michael D.; Marco, Maria L.; Harris, Linda J.
Abstract: The impact of plant development, environmental conditions at the time of inoculation, and inoculum concentration on survival of attenuated BSL1 Escherichia coli O157:H7 strain ATCC 700728 on field-grown romaine lettuce was evaluated over 3 years. E. coli 700728 was inoculated onto 4- and 6-week-old romaine lettuce plants in the Salinas Valley, CA, at night or the next morning with either low (5 log) or high (7 log) cell numbers per plant to simulate a single aqueous contamination event. At night, when leaf wetness and humidity levels were high, E. coli cell numbers declined by 0.5 log CFU/plant over the first 8–10 h. When applied in the morning, E. coli populations declined up to 2 log CFU/plant within 2 h. However, similar numbers of E. coli were retrieved from lettuce plants at 2 and 7 days. E. coli cell numbers per plant were significantly lower ( P < 0.05) 7 days after application onto 4-week-old compared to 6-week-old plants. E. coli 700728 could be recovered by plating or enrichment from a greater proportion of plants for longer times when inoculated at high compared with low initial concentrations and after inoculation of 6-week-old plants compared with 4-week-old plants, even at the low initial inoculum. A contamination event near harvest or when leaf wetness and humidity levels are high may enhance survivability, even when low numbers of E. coli are introduced. Highlights: Higher percentages of E. coli– positive plants recovered when inoculation was closer to harvest. Higher relative humidity and leaf surface wetness were measured during night inoculation. Short-term smaller initial population declines were observed after night inoculation. E. coli population sizes were similar 2 or more days after night or day inoculation. Probability of detecting E. coli was higher for longer times when inoculated at higher levels.